Does Evaluating Teachers Make a Difference? - Simon Briole; Eric Maurin (Institute of Labor Economics (IZA), 2019)
In France, secondary school teachers are evaluated every six or seven years by senior experts of the Ministry of education. These external evaluations mostly involve the supervision of one class session and a debriefing interview, but have nonetheless a direct impact on teachers' career advancement. In this paper, we show that these evaluations contribute to improving students' performance, especially in math. This effect is seen not only for students taught by teachers the year of their evaluations but also for students taught by the same teachers the subsequent years, suggesting that evaluations improve teachers' core pedagogical skills. These positive effects persist over time and are particularly salient in education priority schools, in contexts where teaching is often very challenging. Overall, a system of light touch evaluations appears to be much more cost-effective than more popular alternatives, such as class size reduction.
Keywords: I20; I28; J24; 330; teacher quality; evaluation; feedback; teaching practices; supervision; education